A Review of Activity-based Disaggregate Travel Demand Models - Negar Rezvany; Marija Kukic; Michel Bierlaire (Findings)
This paper reviews the literature on disaggregated travel demand models from a choice perspective, focusing on activity-based models (ABMs) and synthetic population generators as example approaches to capture these choice dimensions. We discuss the links between these models and elaborate on their integration, emphasizing how advanced population synthesis can address gaps in ABMs. The importance of incorporating multi-person and multi-period contexts to more accurately represent travel behavior is highlighted. Further advances aimed at improving the practical application of these models are also discussed.